153k views
2 votes
Solve for y in terms of x.

2/3y - 4 = x

y = x + 6
y = -x + 4
y = -x + 6
y = x + 4

User Cory
by
4.9k points

1 Answer

2 votes

Answer:


y=(3)/(2) x+6

Explanation:

We are given the following equation and we are supposed to solve y in terms of x. It simpler terms, it means that we have to make y the subject of the equation while x being used in it as it is:


(2)/(3) y-4=x

Taking the constant 4 to the side where x is to get:


(2)/(3) y=x+4

Multiplying the denominator 3 to the other side of the equation to get:


2y=3x+12

Isolating y to make it the subject:


y=(3)/(2) x+(12)/(2)\\ \\y=(3)/(2) x+6

User Galled
by
5.1k points